Fighting Against Risks and Uncertainties: Chinese University Students’ Decision-Making About Study Abroad Under COVID-19 - Shen, Wenqin; Chai, Yilin; Gu, Feifei; Zhang, Kun; Feng, Jing; Liu, Xueting; Mo, Ziyou (Journal of International Students, 2023)
Building on a theoretical model of decision-making under risk and uncertainty, this paper examines how Chinese college students made decisions about international moblity or immobility during the Covid 19 pandemic. The paper finds that among the 118 interviewees, most continued to choose to study abroad, whilst some gave up after getting offers from prestigious Western universities. We further analysed the divergent patterns of two choices which can be explained by resilience to risks and uncertainties and lack of thereof. For those who have given up studying abroad, the symbolic capital and labor market advantages brought by degrees (especially master degrees) from Western universities have become uncertain and offset by the risk of the epidemic. These findings suggest that, in addition to safety, college students will prefer certainty more than before when choosing whether to go abroad and the study abroad landscape may change based on this mindset.